Archean phosphorus liberation induced by iron redox geochemistry - Barry Herschy (Nature Portfolio, 2018)
Phosphorus is presumed to have been a limiting nutrient in the Archean ocean due to binding to iron oxides. Here, the authors show the heating of iron with phosphate results in the reduction of phosphate to the ion phosphite, which is solubilized and ameliorates the issue of a low Archean phosphorus supply.